CD83 acts as immediate early response gene in activated macrophages and exhibits specific intracellular trafficking properties - Langguth, Pia; Peckert, Katrin; Beck, Philipp; Kuhnt, Christine; Draßner, Christina; Deinzer, Andrea; Steinkasserer, Alexander; Wild, Andreas (Biochemical and Biophysical Research Communications, 2023)
Macrophages (MΦ) are remarkably plastic cells, which assume phenotypes in every shade between a pro-inflammatory classical activation, and anti-inflammatory or resolving activation. Therefore, elucidation of mechanisms involved in shaping MΦ plasticity and function is key to understand their role during immunological balance. The immune-modulating CD83 molecule is expressed on activated immune cells and various tissue resident MΦ, rendering it an interesting candidate for affecting MΦ biology. However, in-depth analyses of the precise kinetics and trafficking of CD83 within pro-inflammatory, LPS activated bone-marrow-derived MΦ have not been performed. In this study, we show that activation with LPS leads to a very fast and strong, but transient increase of CD83 expression on these cells. Its expression peaks within 2 h of stimulation and is thereby faster than the early activation antigen CD69. To trace the CD83 trafficking through MΦs, we employed multiple inhibitors, thereby revealing a de novo synthesis and transport of the protein to the cell surface followed by lysosomal degradation, all within 6 h. Moreover, we found a similar expression kinetic and trafficking in human monocyte derived MΦ. This places CD83 at a very early point of MΦ activation suggesting an important role in decisions regarding the subsequent cellular fate.
CRIS-Team Scopus Importer:2023-02-10
Keywords: CD83; expression; intracellular trafficking; lipopolysaccharide; macrophages

CD83 expressed by macrophages is an important immune checkpoint molecule for the resolution of inflammation - Peckert-Maier, Katrin; Langguth, Pia; Strack, Astrid; Stich, Lena; Mühl-Zürbes, Petra; Kuhnt, Christine; Drassner, Christina; Zinser, Elisabeth; Wrage, Marius; Mattner, Jochen; Steinkasserer, Alexander; Royzman, Dmytro; et al. (Frontiers in Immunology, 2023)
Excessive macrophage (M phi) activation results in chronic inflammatory responses or autoimmune diseases. Therefore, identification of novel immune checkpoints on M phi, which contribute to resolution of inflammation, is crucial for the development of new therapeutic agents. Herein, we identify CD83 as a marker for IL-4 stimulated pro-resolving alternatively activated M phi (AAM). Using a conditional KO mouse (cKO), we show that CD83 is important for the phenotype and function of pro-resolving M phi. CD83-deletion in IL-4 stimulated M phi results in decreased levels of inhibitory receptors, such as CD200R and MSR-1, which correlates with a reduced phagocytic capacity. In addition, CD83-deficient M phi upon IL-4 stimulation, show an altered STAT-6 phosphorylation pattern, which is characterized by reduced pSTAT-6 levels and expression of the target gene Gata3. Concomitantly, functional studies in IL-4 stimulated CD83 KO M phi reveal an increased production of pro-inflammatory mediators, such as TNF-alpha, IL-6, CXCL1 and G-CSF. Furthermore, we show that CD83-deficient M phi have enhanced capacities to stimulate the proliferation of allo-reactive T cells, which was accompanied by reduced frequencies of Tregs. In addition, we show that CD83 expressed by M phi is important to limit the inflammatory phase using a full-thickness excision wound healing model, since inflammatory transcripts (e.g. Cxcl1, Il6) were increased, whilst resolving transcripts (e.g. Ym1, Cd200r, Msr-1) were decreased in wounds at day 3 after wound infliction, which reflects the CD83 resolving function on M phi also in vivo. Consequently, this enhanced inflammatory milieu led to an altered tissue reconstitution after wound infliction. Thus, our data provide evidence that CD83 acts as a gatekeeper for the phenotype and function of pro-resolving M phi.
CRIS-Team WoS Importer:2023-03-17

CD83 expression is essential for Treg cell differentiation and stability - Döbbeler, Marina; Koenig, Christina; Krzyzak, Lena; Seitz, Christine; Wild, Andreas; Ulas, Thomas; Bassler, Kevin; Kopelyanskiy, Dmitry; Butterhof, Alina; Kuhnt, Christine; Kreiser, Simon; Stich, Lena; et al. (JCI Insight, 2018)
Foxp3-positive regulatory T cells (Tregs) are crucial for the maintenance of immune homeostasis and keep immune responses in check. Upon activation, Tregs are transferred into an effector state expressing transcripts essential for their suppressive activity, migration, and survival. However, it is not completely understood how different intrinsic and environmental factors control differentiation. Here, we present for the first time to our knowledge data suggesting that Treg-intrinsic expression of CD83 is essential for Treg differentiation upon activation. Interestingly, mice with Treg-intrinsic CD83 deficiency are characterized by a proinflammatory phenotype. Furthermore, the loss of CD83 expression by Tregs leads to the downregulation of Treg-specific differentiation markers and the induction of an inflammatory profile. In addition, Treg-specific conditional knockout mice showed aggravated autoimmunity and an impaired resolution of inflammation. Altogether, our results show that CD83 expression in Tregs is an essential factor for the development and function of effector Tregs upon activation. Since Tregs play a crucial role in the maintenance of immune tolerance and thus prevention of autoimmune disorders, our findings are also clinically relevant.
EVALuna2:36212

CD83 orchestrates immunity toward self and non-self in dendritic cells - Wild, Andreas; Krzyzak, Lena; Peckert, Katrin; Stich, Lena; Kuhnt, Christine; Butterhof, Alina; Seitz, Christine; Mattner, Jochen; Grner, Niklas; Gänsbauer, Maximilian; Purtak, Martin; Soulat, Didier; et al. (JCI Insight, 2019)
Dendritic cells (DCs) are crucial to balance protective immunity and autoimmune inflammatory processes. Expression of CD83 is a well-established marker for mature DCs, although its physiological role is still not completely understood. Using a DC-specific CD83-conditional KO (CD83(Delta DC)) mouse, we provide new insights into the function of CD83 within this cell type. Interestingly, CD83-deficient DCs produced drastically increased IL-2 levels and displayed higher expression of the costimulatory molecules CD25 and OX40L, which causes superior induction of antigen-specific T cell responses and compromises Treg suppressive functions. This also directly translates into accelerated immune responses in vivo. Upon Salmonella typhimurium and Listeria monocytogenes infection, CD83(Delta DC) mice cleared both pathogens more efficiently, and CD83-deficient DCs expressed increased IL-12 levels after bacterial encounter. Using the experimental autoimmune encephalomyelitis model, autoimmune inflammation was dramatically aggravated in CD83(Delta DC) mice while resolution of inflammation was strongly reduced. This phenotype was associated with increased cell influx into the CNS accompanied by elevated Th17 cell numbers. Concomitantly, CD83(Delta DC) mice had reduced Treg numbers in peripheral lymphoid organs. In summary, we show that CD83 ablation on DCs results in enhanced immune responses by dysregulating tolerance mechanisms and thereby impairing resolution of inflammation, which also demonstrates high clinical relevance.
CRIS-Team WoS Importer:2019-11-01

Differential Modulation of Dendritic Cell Biology by Endogenous and Exogenous Aryl Hydrocarbon Receptor Ligands - Sadeghi Shermeh, Atefeh; Royzman, Dmytro; Kuhnt, Christine; Draßner, Christina; Stich, Lena; Steinkasserer, Alexander; Knippertz, Ilka; Wild, Andreas (International Journal of Molecular Sciences, 2023)
The aryl hydrocarbon receptor (AhR) is a decisive regulatory ligand-dependent transcription factor. It binds highly diverse ligands, which can be categorized as either endogenous or exogenous. Ligand binding activates AhR, which can adjust inflammatory responses by modulating immune cells such as dendritic cells (DCs). However, how different AhR ligand classes impact the phenotype and function of human monocyte-derived DCs (hMoDCs) has not been extensively studied in a comparative manner. We, therefore, tested the effect of the representative compounds Benzo(a)pyrene (BP), 6-formylindolo[3,2-b]carbazole (FICZ), and Indoxyl 3-sulfate (I3S) on DC biology. Thereby, we reveal that BP significantly induces a tolerogenic response in lipopolysaccharide-matured DCs, which is not apparent to the same extent when using FICZ or I3S. While all three ligand classes activate AhR-dependent pathways, BP especially induces the expression of negative immune regulators, and subsequently strongly subverts the T cell stimulatory capacity of DCs. Using the CRISPR/Cas9 strategy we also prove that the regulatory effect of BP is strictly AhR-dependent. These findings imply that AhR ligands contribute differently to DC responses and incite further studies to uncover the mechanisms and molecules which are involved in the induction of different phenotypes and functions in DCs upon AhR activation.
CRIS-Team Scopus Importer:2023-05-26
Keywords: aryl hydrocarbon receptor; dendritic cells; endogenous ligands; exogenous ligands

Effect of sCD83 on macrophages in corneal high-risk transplantation - Schoenberg, Alfrun; Peckert-Maier, Katrin; Wild, Andreas; Royzman, Dmytro; Braun, Gabriele; Stich, Lena; Cursiefen, Claus; Steinkasserer, Alexander; Bock, Felix; Zinser, Elisabeth (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2021)
CRIS-Team WoS Importer:2021-10-15

Endogenous Expression of the Human CD83 Attenuates EAE Symptoms in Humanized Transgenic Mice and Increases the Activity of Regulatory T Cells - Zinser, Elisabeth; Naumann, Ronald; Wild, Andreas; Michalski, Julia; Deinzer, Anja; Stich, Lena; Kuhnt, Christine; Steinkasserer, Alexander; Knippertz, Ilka (Frontiers in Immunology, 2019)
The CD83 is a type I membrane protein and part of the immunoglobulin superfamily of receptors. CD83 is involved in the regulation of antigen presentation and dendritic cell dependent allogeneic T cell proliferation. A soluble form of CD83 inhibits dendritic cell maturation and function. Furthermore, CD83 is expressed on activated B cells, T cells, and in particular on regulatory T cells. Previous studies on murine CD83 demonstrated this molecule to be involved in several immune-regulatory processes, comprising that CD83 plays a key role in the development and function of different immune cells. In order to get further insights into the function of the human CD83 and to provide preclinical tools to guide the function of CD83/sCD83 for therapeutic purposes we generated Bacterial Artificial Chromosomes (BAC) transgenic mice. BACs are excellent tools for manipulating large DNA fragments and are utilized to engineer transgenic mice by pronuclear injection. Two different founders of BAC transgenic mice expressing human CD83 (BAC-hCD83(tg) mice) were generated and were examined for the hCD83 expression on different immune cells as well as both the in vitro and in vivo role of human CD83 (hCD83) in health and disease. Here, we found the hCD83 molecule to be present on activated DCs, B cells and subtypes of CD4(+) T cells. CD8(+) T cells, on the other hand, showed almost no hCD83 expression. To address the function of hCD83, we performed in vitro mixed lymphocyte reactions (MLR) as well as suppression assays and we used the in vivo model of experimental autoimmune encephalomyelitis (EAE) comparing wild-type and hCD83-BAC mice. Results herein showed a clearly diminished capacity of hCD83-BAC-derived T cells to proliferate accompanied by an enhanced activation and suppressive activity of hCD83-BAC-derived Tregs. Furthermore, hCD83-BAC mice were found to recover faster from EAE-associated symptoms than wild-type mice, encouraging the relevance also of the hCD83 as a key molecule for the regulatory phenotype of Tregs in vitro and in vivo.
CRIS-Team WoS Importer:2019-07-12

Environment affects dendritic cells' response via Aryl Hydrocarbon Receptor ligands: a comparison between endogenous and exogenous ligands - Sadeghi Shermeh, Atefeh; Wild, Andreas; Michalski, Julia; Steinkasserer, Alexander (EUROPEAN JOURNAL OF IMMUNOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-27

Four-and-a-Half LIM-Domain Protein 2 (FHL2) Induces Neuropeptide Y (NPY) in Macrophages in Visceral Adipose Tissue and Promotes Diet-Induced Obesity - Sommer, Judith; Ehnis, Hanna; Seitz, Tatjana; Schneider, Julia; Wild, Andreas; Moceri, Sandra; Buechler, Christa; Bozec, Aline; Weber, Georg; Merkel, Susanne; Beckervordersandforth, Ruth; Steinkasserer, Alexander; et al. (International Journal of Molecular Sciences, 2023)
Obesity is characterized by the expansion of the adipose tissue, usually accompanied by inflammation, with a prominent role of macrophages infiltrating the visceral adipose tissue (VAT). This chronic inflammation is a major driver of obesity-associated comorbidities. Four-and-a-half LIM-domain protein 2 (FHL2) is a multifunctional adaptor protein that is involved in the regulation of various biological functions and the maintenance of the homeostasis of different tissues. In this study, we aimed to gain new insights into the expression and functional role of FHL2 in VAT in diet-induced obesity. We found enhanced FHL2 expression in the VAT of mice with Western-type diet (WTD)-induced obesity and obese humans and identified macrophages as the cellular source of enhanced FHL2 expression in VAT. In mice with FHL2 deficiency (FHL2KO), WTD feeding resulted in reduced body weight gain paralleled by enhanced energy expenditure and uncoupling protein 1 (UCP1) expression, indicative of activated thermogenesis. In human VAT, FHL2 was inversely correlated with UCP1 expression. Furthermore, macrophage infiltration and the expression of the chemokine MCP-1, a known promotor of macrophage accumulation, was significantly reduced in WTD-fed FHL2KO mice compared with wild-type (wt) littermates. While FHL2 depletion did not affect the differentiation or lipid metabolism of adipocytes in vitro, FHL2 depletion in macrophages resulted in reduced expressions of MCP-1 and the neuropeptide Y (NPY). Furthermore, WTD-fed FHL2KO mice showed reduced NPY expression in VAT compared with wt littermates, and NPY expression was enhanced in VAT resident macrophages of obese individuals. Stimulation with recombinant NPY induced not only UCP1 expression and lipid accumulation but also MCP-1 expression in adipocytes. Collectively, these findings indicate that FHL2 is a positive regulator of NPY and MCP-1 expression in macrophages and herewith closely linked to the mechanism of obesity-associated lipid accumulation and inflammation in VAT. Thus, FHL2 appears as a potential novel target to interfere with the macrophage–adipocyte crosstalk in VAT for treating obesity and related metabolic disorders.
CRIS-Team Scopus Importer:2023-11-03
Keywords: adipocytes; FHL2; macrophages; MCP-1; NPY; obesity; thermogenesis

Functional modulation of regulatory T cells (Tregs) and analyses of the underlying mechanisms - Marosán, Anita; Steinkasserer, Alexander; Wild, Andreas (EUROPEAN JOURNAL OF IMMUNOLOGY, 2022)
CRIS-Team WoS Importer:2023-02-17

Microglial expression of CD83 governs cellular activation and restrains neuroinflammation in experimental autoimmune encephalomyelitis - Sinner, Pia; Peckert-Maier, Katrin; Mohammadian, Hashem; Kuhnt, Christine; Draßner, Christina; Panagiotakopoulou, Vasiliki; Rauber, Simon; Linnerbauer, Mathias; Haimon, Zhana; Royzman, Dmytro; Kronenberg-Versteeg, Deborah; Ramming, Andreas; et al. (Nature Communications, 2023)
Microglial activation during neuroinflammation is crucial for coordinating the immune response against neuronal tissue, and the initial response of microglia determines the severity of neuro-inflammatory diseases. The CD83 molecule has been recently shown to modulate the activation status of dendritic cells and macrophages. Although the expression of CD83 is associated with early microglia activation in various disease settings, its functional relevance for microglial biology has been elusive. Here, we describe a thorough assessment of CD83 regulation in microglia and show that CD83 expression in murine microglia is not only associated with cellular activation but also with pro-resolving functions. Using single-cell RNA-sequencing, we reveal that conditional deletion of CD83 results in an over-activated state during neuroinflammation in the experimental autoimmune encephalomyelitis model. Subsequently, CD83-deficient microglia recruit more pathogenic immune cells to the central nervous system, deteriorating resolving mechanisms and exacerbating the disease. Thus, CD83 in murine microglia orchestrates cellular activation and, consequently, also the resolution of neuroinflammation.
CRIS-Team Scopus Importer:2023-08-11

Pre-incubation of corneal donor tissue with sCD83 improves graft survival via the induction of alternatively activated macrophages and tolerogenic dendritic cells - Peckert-Maier, Katrin; Schoenberg, Alfrun; Wild, Andreas; Royzman, Dmytro; Braun, Gabriele; Stich, Lena; Hadrian, Karina; Tripal, Philipp; Cursiefen, Claus; Steinkasserer, Alexander; Zinser, Elisabeth; Bock, Felix (American Journal of Transplantation, 2021)
Immune responses reflect a complex interplay of cellular and extracellular components which define the microenvironment of a tissue. Therefore, factors that locally influence the microenvironment and re-establish tolerance might be beneficial to mitigate immune-mediated reactions, including the rejection of a transplant. In this study, we demonstrate that pre-incubation of donor tissue with the immune modulator soluble CD83 (sCD83) significantly improves graft survival using a high-risk corneal transplantation model. The induction of tolerogenic mechanisms in graft recipients was achieved by a significant upregulation of Tgfb, Foxp3, II27, and II10 in the transplant and an increase of regulatory dendritic cells (DCs), macrophages (M phi) and T cells (Tregs) in eye-draining lymph nodes. The presence of sCD83 during in vitro DC and M phi generation directed these cells toward a tolerogenic phenotype leading to reduced proliferation-stimulating activity in MLRs. Mechanistically, sCD83 induced a tolerogenic M phi and DC phenotype, which favors Treg induction and significantly increased transplant survival after adoptive cell transfer. Conclusively, pre-incubation of corneal grafts with sCD83 significantly prolongs graft survival by modulating recipient M phi and DCs toward tolerance and thereby establishing a tolerogenic microenvironment. This functional strategy of donor graft pre-treatment paves the way for new therapeutic options in the field of transplantation.
CRIS-Team WoS Importer:2021-10-01

Pre-incubation of corneal donor tissue with soluble CD83 improves graft survival via the induction of pro-resolving macrophages - Peckert-Maier, Katrin; Schoenberg, Alfrun; Wild, Andreas; Royzman, Dmytro; Braun, Gabriele; Hadrian, Karina; Tripal, Philipp; Cursiefen, Claus; Steinkasserer, Alexander; Zinser, Elisabeth; Bock, Felix (WOUND REPAIR AND REGENERATION, 2022)
CRIS-Team WoS Importer:2022-09-16

Soluble CD83 improves and accelerates wound healing by the induction of pro-resolving macrophages - Royzman, Dmytro; Peckert-Maier, Katrin; Stich, Lena; König, Christina; Wild, Andreas; Tauchi, Miyuki; Ostalecki, Christian; Kiesewetter, Franklin; Seyferth, Stefan; Lee, Geoffrey; Eming, Sabine A.; Fuchs, Maximilian; et al. (Frontiers in Immunology, 2022)
To facilitate the recovery process of chronic and hard-to-heal wounds novel pro-resolving treatment options are urgently needed. We investigated the pro-regenerative properties of soluble CD83 (sCD83) on cutaneous wound healing, where sCD83 accelerated wound healing not only after systemic but also after topical application, which is of high therapeutic interest. Cytokine profile analyses revealed an initial upregulation of inflammatory mediators such as TNFα and IL-1β, followed by a switch towards pro-resolving factors, including YM-1 and IL-10, both expressed by tissue repair macrophages. These cells are known to mediate resolution of inflammation and stimulate wound healing processes by secretion of growth factors such as epidermal growth factor (EGF) and vascular endothelial growth factor (VEGF), which promote vascularization as well as fibroblast and keratinocyte differentiation. In conclusion, we have found strong wound healing capacities of sCD83 beyond the previously described role in transplantation and autoimmunity. This makes sCD83 a promising candidate for the treatment of chronic- and hard-to-heal wounds.
CRIS-Team Scopus Importer:2022-10-28
Keywords: CD83; macrophages; stem cells; therapy; tissue regeneration; wound healing

Soluble CD83 modulates human-monocyte-derived macrophages toward alternative phenotype, function, and metabolism. - Peckert-Maier, Katrin; Wild, Andreas; Sprißler, Laura; Fuchs, Maximilian; Beck, Philipp; Auger, Jean-Philippe; Sinner, Pia; Strack, Astrid; Mühl-Zürbes, Petra; Ramadan, Ntilek; Kunz, Meik; Krönke, Gerhard; et al. (Frontiers in Immunology, 2023)
Alterations in macrophage (Mφ) polarization, function, and metabolic signature can foster development of chronic diseases, such as autoimmunity or fibrotic tissue remodeling. Thus, identification of novel therapeutic agents that modulate human Mφ biology is crucial for treatment of such conditions. Herein, we demonstrate that the soluble CD83 (sCD83) protein induces pro-resolving features in human monocyte-derived Mφ biology. We show that sCD83 strikingly increases the expression of inhibitory molecules including ILT-2 (immunoglobulin-like transcript 2), ILT-4, ILT-5, and CD163, whereas activation markers, such as MHC-II and MSR-1, were significantly downregulated. This goes along with a decreased capacity to stimulate alloreactive T cells in mixed lymphocyte reaction (MLR) assays. Bulk RNA sequencing and pathway analyses revealed that sCD83 downregulates pathways associated with pro-inflammatory, classically activated Mφ (CAM) differentiation including HIF-1A, IL-6, and cytokine storm, whereas pathways related to alternative Mφ activation and liver X receptor were significantly induced. By using the LXR pathway antagonist GSK2033, we show that transcription of specific genes (e.g., PPARG, ABCA1, ABCG1, CD36) induced by sCD83 is dependent on LXR activation. In summary, we herein reveal for the first time mechanistic insights into the modulation of human Mφ biology by sCD83, which is a further crucial preclinical study for the establishment of sCD83 as a new therapeutical agent to treat inflammatory conditions.
EVALuna2:549687

Soluble CD83 promotes cutaneous wound healing in an IDO-and beta-catenindependent manner - Royzman, Dmytro; Peckert-Maier, K.; Stich, L.; Wild, Andreas; Ostalecki, C.; Kiesewetter, Franklin; Seyferth, Stefan; Lee, Geoffrey; Eming, S. A.; Berking, Carola; Zinser, Elisabeth; Steinkasserer, Alexander (EXPERIMENTAL DERMATOLOGY, 2022)
CRIS-Team WoS Importer:2022-03-04

The CD83 Molecule – An Important Immune Checkpoint - Grosche, Linda; Knippertz, Ilka; König, Christina; Royzman, Dmytro; Wild, Andreas; Zinser, Elisabeth; Sticht, Heinrich; Muller, Yves; Steinkasserer, Alexander; Lechmann, Matthias (Frontiers in Immunology, 2020)
The CD83 molecule has been identified to be expressed on numerous activated immune cells, including B and T lymphocytes, monocytes, dendritic cells, microglia, and neutrophils. Both isoforms of CD83, the membrane-bound as well as its soluble form are topic of intensive research investigations. Several studies revealed that CD83 is not a typical co-stimulatory molecule, but rather plays a critical role in controlling and resolving immune responses. Moreover, CD83 is an essential factor during the differentiation of T and B lymphocytes, and the development and maintenance of tolerance. The identification of its interaction partners as well as signaling pathways have been an enigma for the last decades. Here, we report the latest data on the expression, structure, and the signaling partners of CD83. In addition, we review the regulatory functions of CD83, including its striking modulatory potential to maintain the balance between tolerance versus inflammation during homeostasis or pathologies. These immunomodulatory properties of CD83 emphasize its exceptional therapeutic potential, which has been documented in specific preclinical disease models.
CRIS-Team Scopus Importer:2020-05-08
Keywords: autoimmunity; CD83; immune tolerance; Treg cells; viral escape mechanism

The CD83 molecule expressed by dendritic cells is a checkpoint to regulate resolution of inflammation as well as homeostasis within periphery and CNS - Wild, Andreas; Krzyzak, Lena; Mattner, Jochen; Winkler, Thomas; Nitschke, Lars; Steinkasserer, Alexander (2018)
EVALuna2:36214

The soluble CD83 molecule accelerates wound closure and improves wound healing quality - Royzman, Dmytro; Peckert-Maier, Katrin; Stich, Lena; Wild, Andreas; Ostalecki, Christian; Seyferth, Stefan; Eming, Sabine A.; Fuchs, Maximilian; Kunz, Meik; Sturmer, Ewa K.; Peters, Eva M. J.; Berking, Carola; et al. (WOUND REPAIR AND REGENERATION, 2022)
CRIS-Team WoS Importer:2022-09-16

The soluble CD83 protein prevents bone destruction by inhibiting the formation of osteoclasts and inducing resolution of inflammation in arthritis - Royzman, Dmytro; Andreev, Darja; Stich, Lena; Peckert, Katrin; Wild, Andreas; Zinser, Elisabeth; Mühl-Zürbes, Petra; Jones, Evan; Adam, Susanne; Frey, Silke; Fuchs, Maximilian; Kunz, Meik; et al. (Frontiers in Immunology, 2022)
Here we show that soluble CD83 induces the resolution of inflammation in an antigen-induced arthritis (AIA) model. Joint swelling and the arthritis-related expression levels of IL-1 beta, IL-6, RANKL, MMP9, and OC-Stamp were strongly reduced, while Foxp3 was induced. In addition, we observed a significant inhibition of TRAP(+) osteoclast formation, correlating with the reduced arthritic disease score. In contrast, cell-specific deletion of CD83 in human and murine precursor cells resulted in an enhanced formation of mature osteoclasts. RNA sequencing analyses, comparing sCD83- with mock treated cells, revealed a strong downregulation of osteoclastogenic factors, such as Oc-Stamp, Mmp9 and Nfatc1, Ctsk, and Trap. Concomitantly, transcripts typical for pro-resolving macrophages, e.g., Mrc1/2, Marco, Klf4, and Mertk, were upregulated. Interestingly, members of the metallothionein (MT) family, which have been associated with a reduced arthritic disease severity, were also highly induced by sCD83 in samples derived from RA patients. Finally, we elucidated the sCD83-induced signaling cascade downstream to its binding to the Toll-like receptor 4/(TLR4/MD2) receptor complex using CRISPR/Cas9-induced knockdowns of TLR4/MyD88/TRIF and MTs, revealing that sCD83 acts via the TRIF-signaling cascade. In conclusion, sCD83 represents a promising therapeutic approach to induce the resolution of inflammation and to prevent bone erosion in autoimmune arthritis.
CRIS-Team WoS Importer:2022-09-09

Tilting the Balance: Therapeutic Prospects of CD83 as a Checkpoint Molecule Controlling Resolution of Inflammation - Peckert-Maier, Katrin; Royzman, Dmytro; Langguth, Pia; Marosán, Anita; Strack, Astrid; Sadeghi Shermeh, Atefeh; Steinkasserer, Alexander; Zinser, Elisabeth; Wild, Andreas (International Journal of Molecular Sciences, 2022)
Chronic inflammatory diseases and transplant rejection represent major challenges for modern health care. Thus, identification of immune checkpoints that contribute to resolution of inflammation is key to developing novel therapeutic agents for those conditions. In recent years, the CD83 (cluster of differentiation 83) protein has emerged as an interesting potential candidate for such a “pro-resolution” therapy. This molecule occurs in a membrane-bound and a soluble isoform (mCD83 and sCD83, respectively), both of which are involved in resolution of inflammation. Originally described as a maturation marker on dendritic cells (DCs), mCD83 is also expressed by activated B and T cells as well as regulatory T cells (Tregs) and controls turnover of MHC II molecules in the thymus, and thereby positive selection of CD4+ T cells. Additionally, it serves to confine overshooting (auto-)immune responses. Consequently, animals with a conditional deletion of CD83 in DCs or regulatory T cells suffer from impaired resolution of inflammation. Pro-resolving effects of sCD83 became evident in pre-clinical autoimmune and transplantation models, where application of sCD83 reduced disease symptoms and enhanced allograft survival, respectively. Here, we summarize recent advances regarding CD83-mediated resolution of inflammatory responses, its binding partners as well as induced signaling pathways, and emphasize its therapeutic potential for future clinical trials.
CRIS-Team Scopus Importer:2022-01-14
Keywords: Adoptive transfer; CD83; IDO/TGF-β-axis; Pro-resolving macrophages; Resolution of inflammation; Transplantation